Evaluation of the validity of large-scale serial sectioning TEM for three-dimensional reconstruction of rice mesophyll cells and chloroplasts. - Yamane, Koji; Oi, Takao; Taniguchi, Mitsutaka (Protoplasma, 2022)
Serial sectioning transmission electron microscopy (ssTEM) is a classical method of 3D reconstruction using serial sections obtained with an ultramicrotome. However, producing a long ribbon with homogeneity is difficult. Here, ultramicrotome movement was suspended after producing a ribbon of 15–30 serial sections (cutting intervals, 100 nm), and then, the ribbon was mounted on an individual one-slot grid. However, as this ssTEM method may include influencing factors such as incorrect intervals of section thickness and distortion of sections, which is produced by cutting sections using a diamond knife and beam interaction under TEM observation, qualitative and quantitative data on rice mesophyll cells and chloroplasts were compared with those obtained from a focused ion beam scanning electron microscopy (FIB-SEM) (cutting intervals, 50 nm). No structural distortion in 3D models was observed. In addition, no significant differences in the volume and surface area were observed between the two methods. The surface to volume ratio was significantly affected by the increase in section thickness, but not the difference of methodologies. Our method was useful for observing large volumes of plant cells and organelles, leading to the identification of various sizes and types of chloroplasts. The formation of a chloroplast pocket, which is a structure surrounding other intracellular compartments, was confirmed in rice leaves grown under moderate growth conditions using the ssTEM method. As only four out of 90 chloroplasts formed pocket structures, the formation was considered to be rare under the applied moderate growth conditions.